Teenage Mutant Ninja Turtles 3 - Koteas, Elias; Turco, Paige; New Line Home Entertainment ([United States?] : New Line Home Entertainment, 2002)
When a magic scepter accidentally transports April back in time to 17th Century Japan, the boys take off in hot pursuit.
Originally released as a motion picture in 1993.
Based on the characters created by Kevin Eastman and Peter Laird.
Directd by David Chan.
Elias Koteas, Paige Turco.
MPAA rating: PG; for swashbuckling violence and mild language.
DVD.
Keywords: Teenage Mutant Ninja Turtles (Fictitious characters) -- Juvenile films; Teenage Mutant Ninja Turtles (Fictitious characters); Films for the hearing impaired; Films for the hearing impaired; Juvenile works; Children's films